2018
DOI: 10.1021/jacs.8b03733
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Structure of Carbon Nanothreads Analyzed by Advanced Solid-State NMR

Abstract: Carbon nanothreads are a new type of one-dimensional sp-carbon nanomaterial formed by slow compression and decompression of benzene. We report characterization of the chemical structure of C-enriched nanothreads by advanced quantitative, selective, and two-dimensional solid-state nuclear magnetic resonance (NMR) experiments complemented by infrared (IR) spectroscopy. The width of the NMR spectral peaks suggests that the nanothread reaction products are much more organized than amorphous carbon. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…The interplanar spacings of the first-order reflections in SAED patterns are 5.7 ± 0.1 Å, which is consistent with the spacings predicted for several candidate degree-6 nanothread structures ( Figures S2-S5), when accounting for thermal expansion and beam-induced dilation of the lattice; these include the structures favored by a detailed solid-state NMR analysis. [26][27] The other reflections in Figure 4a index close to the Figure 1. Nanothread Carbon K-edge Electron Energy−Loss Spectrum.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The interplanar spacings of the first-order reflections in SAED patterns are 5.7 ± 0.1 Å, which is consistent with the spacings predicted for several candidate degree-6 nanothread structures ( Figures S2-S5), when accounting for thermal expansion and beam-induced dilation of the lattice; these include the structures favored by a detailed solid-state NMR analysis. [26][27] The other reflections in Figure 4a index close to the Figure 1. Nanothread Carbon K-edge Electron Energy−Loss Spectrum.…”
Section: Resultsmentioning
confidence: 60%
“…An amorphous phase is not evident in the electron diffraction patterns nor in the NMR spectra. 26 In contrast, disregistry in nanothread packing should give a diffuse background that follows the overall lattice symmetry, as is observed for adamantane and C 60 . 42 Extensive diffraction simulations along [0001] were performed each with a single thread type within a supercell large enough to capture some of the effects of disregistry, shown in Figures S6−S8 plus one illustrative case in Figure 4b and Figure 4c.…”
Section: Resultsmentioning
confidence: 99%
“…6). Increasing the filament number further leads to a much larger coil radius for the outermost filaments, which results in a more rapid increase in the tensile strain (as seen in bundle- 19). In comparison, the compressive strain exhibits a gradual increase for all nanothread-A bundles.…”
Section: Optimum Mechanical Energy Storage In Nanothread Bundlementioning
confidence: 99%
“…In 2015, a class of one-dimensional (1D) carbon nanostructure -the carbon nanothread-was reported 18 . Although experimental efforts are still ongoing to characterize the atomic structures of carbon nanothreads 19,20 , first-principle calculations have systematically enumerated the potential configuration of carbon nanothreads, including the fully saturated (or degree-6) and partially saturated (or degree-4) structures 21,22 . Unlike the sp 2 bonding in CNT, the carbon nanothread is an ultra-thin sp 3bonded carbon structure.…”
mentioning
confidence: 99%
“…E-mail: fanetti@lens.uni.it; roberto.bini@uni.it; Fax: +390554572489; Tel: +390554572436 2D lattice (a ¼ 6.5Å) characterized by a correlation length of several tens of nm, but denitely lower, #2.5 nm, along the threads. 17,18 A consequence of the mechanism described above leading to the nanothread formation is that the reaction cannot be quantitative, competing with the topochemical one which leads to the formation of amorphous hydrogenated carbon (a-C:H). 19,20 Aer the discovery of nanothread formation from benzene, computational and experimental studies revealed the possibility of synthesising nanothreads from a large number of aromatics and heteroaromatics.…”
Section: Introductionmentioning
confidence: 99%